A microsatellite study in the Łęgucki Młyn/Popielno hybrid zone reveals no genetic differentiation between two chromosome races of the common shrew (Sorex araneus) - Moska, Magdalena (Springer-Verlag, 2011)
This study investigated a chromosome hybrid zone between two chromosomal races of the common shrew (Sorex araneus). Gene flow and genetic structure of the hybrid zone, located in the northeast of Poland, were studied using seven polymorphic autosomal microsatellite loci (L9, L14, L33, L45, L67, L68, L97) and a Y-linked microsatellite locus (L8Y). Seventy-five animals (46 of the Łęgucki Młyn race and 29 of the Popielno race) from nine different localities were examined and the data were analyzed using hierarchical AMOVA and F-statistic. The studied microsatellite loci and races (divided into nine geographical populations) were characterized by observed heterozygosity (H (O)), expected heterozygosities within (H (S)), and between (H (T)) populations, inbreeding coefficient (F (IS)), fixation index (F (ST)), and average allelic richness (A). We found that genetic structuring within and between the two chromosome races were weak and non-significant. This finding and unconstrained gene flow between the races indicates a high level of migration within the Łęgucki Młyn/Popielno hybrid zone, suggesting that evolutionarily important genetic structuring does not occur in interracial zones where races which are not genetically distinct come into contact.